Pengaruh Kompetensi Guru terhadap Pendidikan Karakter Di TPQ - Mahrus Hadi (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
One of the most crucial elements in the classroom learning process is the teacher; without a teacher, learning cannot take place. The teacher plays a crucial role in the learning process not only because she or he teaches the material, but also because she or he teaches students about character and trains them to be good people and smart citizens. Innovative and engaging learning models and methods must be available to teachers and understood. The goal of this study is to find out: 1) To ascertain the character education of TPQ students; 2) To ascertain the competence of TPQ teachers; and 3) To ascertain the impact of teacher competence on TPQ student character education. The most important way to deal with this examination is the socio-social methodology. Although the curriculum may be provided by a policy-making organization, it is the instructor's responsibility to present the material. The educator's method of disseminating and transferring knowledge so that it can be fully accepted by students based on their level of education determines the success of the packaged material.